2022
DOI: 10.1162/qss_a_00175
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of university affiliation discrepancies between four bibliographic databases—Scopus, Web of Science, Dimensions, and Microsoft Academic

Abstract: Research managers benchmarking universities against international peers face the problem of affiliation disambiguation. Different databases have taken separate approaches to this problem and discrepancies exist between them. Bibliometric data sources typically conduct a disambiguation process that unifies variant institutional names and those of its sub-units so that researchers can then search all records from that institution using a single unified name. This study examined affiliation discrepancies between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Scopus is the largest database that includes abstracts to literature citations that can be searched and organized based on the needs of researchers (Henriquez et al, 2022;Stefanis et al, 2022;Thelwall & Sud, 2022). Scopus is under the auspices of Elsevier (Purnell, 2022;Caputo & Kargina, 2022). In addition to bibliometric studies, this research also uses literature review.…”
Section: Research Methods General Backgroundmentioning
confidence: 99%
“…Scopus is the largest database that includes abstracts to literature citations that can be searched and organized based on the needs of researchers (Henriquez et al, 2022;Stefanis et al, 2022;Thelwall & Sud, 2022). Scopus is under the auspices of Elsevier (Purnell, 2022;Caputo & Kargina, 2022). In addition to bibliometric studies, this research also uses literature review.…”
Section: Research Methods General Backgroundmentioning
confidence: 99%
“…The institution matching in this study relies on Scopus Affiliation Identifier that assigns an 8-digit AFID to each institution and links variants to the main AFID. Institutional disambiguation is very difficult and up to one in five publications can have discrepancies in author affiliations between the major bibliographic databases [25]. Scopus definitely has room for improvement as is the case for other bibliographic databases [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…Guerrero‐Bote et al (2021) compared Scopus and Dimensions at country and organizational level, finding that Dimensions lacked affiliation data in more than half of the publications. Finally, Purnell (2022) showed that large databases such as Dimensions and Microsoft Academic have more affiliation discrepancies than Scopus or Web of Science.…”
Section: Literature Reviewmentioning
confidence: 99%